Rancang Bangun E-Care Aplikasi Konseling Online Berbasis Website Dengan Menggunakan Metode Client Centered Pada Universitas Dinamika - Gusti Adistriani; Erwin Sutomo; Bambang Hariadi (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2021)
Counseling Guidance section on campus has the function of helping and addressing the problems that students have both academically, socially, personally. The many problems experienced have an impact on the development of academic value, personality and social life of students. So with this, it is expected that students can re-focus on achievement and actively socialize. But many students do not do counseling even though they have problems. Various reasons include being ashamed, not trusting a counsellor, fearing the negative stigma of her peers and not knowing about counseling. So to solve the problem, an application was created that helps students to do counseling online called E-care. This application is built by Client Centered method, because in this method counselors can apply the necessary properties such as sincerity, warmth, nonposesive acceptance and accurate empathy through text/non-verbal in the chat process. Based on the results and trials during the E-care application development process obtained results in the form of a website application that can be used for online counseling. In the application there are several features such as MBTI test and anxiety level test. As well as some of the reports produced are medical records reports and monthly recap reports.